Design and Build of an Information Sharing Application at the Palembang TV (PAL TV) Office Based on Android - Higyendra Rizki (Jurnal Jaringan Komputer dan Keamanan, 2025)
PT Palembang TV is an electronic media company or organization whose main service is to disseminate information. Sharing activities within this company currently do not have a centralized information service. This is especially true for employees who need an integrated official information medium for job information, news, culture, rules, history, and even group discussions that have not been professionally accommodated well. This study aims to produce an application that can help PT. Palembang TV to provide convenience in sharing information among employees, so that the information transfer process is expected to be faster and clearer. This research was conducted from February to April 2020. For data collection, the authors came directly to the research location at Palembang TV, Palembang City. The software used in the research is Microsoft Office 2016, Xampp Webserver, HTML5, PHP, Framework7, and Cordova. This study uses data collection methods of observation, interviews, and documentation. The results obtained with the information sharing application at the Palembang TV office are the existence of an official medium that is mobile and capable of reaching all staff and leaders at PT. Palembang TV. This ensures that the process of communication and professional dissemination of internal information can be well-integrated and capable of increasing togetherness with structured and clear information.